Biocompatibility of a self-assembled glycol chitosan nanogel - Pereira, Paula (2015)
The research of chitosan-based nanogel for biomedical applications has grown exponentially in the last years; however, its biocompatibility is still insufficiently reported. Hence, the present work provides a thorough study of the biocompatibility of a glycol chitosan (GC) nanogel. The obtained results showed that GC nanogel induced slight decrease on metabolic activity of RAW, 3T3 and HMEC cell cultures, although no effect on cell membrane integrity was verified. The nanogel does not promote cell death by apoptosis and/or necrosis, exception made for the HMEC cell line challenged with the higher GC nanogel concentration. Cell cycle arrest on G1 phase was observed only in the case of RAW cells. Remarkably, the nanogel is poorly internalized by bone marrow derived macrophages and does not trigger the activation of the complement system. GC nanogel blood compatibility was confirmed through haemolysis and whole blood clotting time assays. Overall, the results demonstrated the safety of the use of the GC nanogel as drug delivery system.